Estudo de um motor ciclo diesel monocilíndrico bi-combustível - Rosa, Josimar Souza (Universidade do Vale do Rio dos Sinos, 2014)
This study aims to analyze the operation of an internal combustion engine (diesel cycle) with partial mixtures of diesel oil and natural gas, and oil vegetable soybean and natural gas. The tests were carry in an engine Agrale model M90, monocilynder, coupled to alternator, and which charged a bank of resistors load. The analyses include performance fuel consumption, power and gas emissions of nitrogen oxides, sulfur dioxides, carbon monoxide, and other gases, as well the analysis of the smoke opacity. Results showed that it is feasible to use natural gas in diesel cycle engines without removing the original diesel injection system, generating a considerable reduction in specific emissions of nitrogen oxides, without loss of Power, but resulting in incomplete combustion at high percentages replacement of liquid fuel for natural gas. Generally, the Best result for efficiency was possible with replacement percentage of 43,7% of diesel per natural gas, when the generation setting showed efficiency equal at 33,17%. The smoke opacity was reduced significantly when operated in dual fuel both diesel and natural gas as soybean oil and natural gas.
Keywords: Motor diesel; Bi-combustível; Mono-combustível; Diesel engine; Dual-fuel; Mono-fuel; ACCNPQ::Engenharias::Engenharia Mecânica